Participant experiences of mindfulness-based childbirth education: a qualitative study - Fisher, C.; Hauck, Yvonne; Bayes, Sara; Byrne, J. (BioMed Central Ltd, 2012)
Background: Childbirth is an important transitional life event, but one in which many women are dissatisfied stemming in part from a sense that labour is something that happens to them rather than with them. Promoting maternal satisfaction with childbirth means equipping women with communication and decision making skills that will enhance their ability to feel involved in their labour. Additionally, traditional antenatal education does not necessarily prepare expectant mothers and their birth support partner adequately for birth. Mindfulness-based interventions appear to hold promise in addressing these issues. Mindfulness-based Child Birth Education (MBCE) was a pilot intervention combining skills-based antenatal education and Mindfulness Based Stress Reduction. Participant experiences of MBCE, both of expectant mothers and their birth support partners are the focus of this article. Methods: A generic qualitative approach was utilised for this study. Pregnant women between 18 and 28 weeks gestation, over 18 years of age, nulliparous with singleton pregnancies and not taking medication for a diagnosed mental illness or taking illicit drugs were eligible to undertake the MBCE program which was run in a metropolitan city in Australia. Focus groups with 12 mothers and seven birth support partners were undertaken approximately four months after the completion of MBCE. Audio recordings of the groups were transcribed verbatim and analysed thematically using the method of constant comparison by all four authors independently and consensus on analysis and interpretation arrived at through team meetings.Results: A sense of both ‘empowerment’ and ‘community’ were the essences of the experiences of MBCE both for mothers and their birth support partner and permeated the themes of ‘awakening my existing potential’ and ‘being in a community of like-minded parents’. Participants suggested that mindfulness techniques learned during MBCE facilitated their sense of control during birth, and the content and pedagogical approach of MBCE enabled them to be involved in decision making during the birth. The pedagogical approach also fostered a sense of community among participants which extended into the postnatal period. Conclusions: MBCE has the potential to empower women to become active participants in the birthing process, thus addressing common concerns regarding lack of control and satisfaction with labour and facilitate peer support into the postnatal period. Further education of health professionals may be needed to ensure that they respond positively to those women and birth support partners who remain active in decision making during birth.